PERAN SISTEM INFORMASI MANAJEMEN DALAM PENINGKATAN AKUNTABILITAS PELAPORAN ADMINISTRASI GURU DI MAN KOTA LHOKSEUMAWE - Yusdarni, Yusdarni; Almuhajir, Almuhajir; Rahmah, Syarifah (Adaara: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to explain the implementation of the Management Information System (MIS), supervision of the MIS, and the impact of the MIS in improving the accountability of teacher administrative reporting at MAN Kota Lhokseumawe. This study uses a descriptive qualitative method with a descriptive approach implemented at MAN Kota Lhokseumawe, which was conducted from February to April 2025. Data sources consist of primary data obtained directly from informants (teachers, Head of Administration, and Deputy Curriculum) and secondary data from various literature and relevant documents. Data collection was carried out through three main techniques: observation of interactions between teachers, information systems, and administrative processes, open interviews with informants, and documentation in the form of tracing written records and authentic evidence of the role of the MIS in improving teacher administrative accountability. The results of the study indicate that the implementation of the MIS has been carried out systematically through the stages of planning, organizing, implementing, and evaluating. Each teacher has a personal account to access E-Kinerja, with the obligation to upload administration in the form of workbooks 1-4 covering various learning devices. Supervision is carried out directly by the head of the Madrasah with data validation, a warning system for delays, and periodic evaluations through quarterly meetings. The impact of using SIM is very positive, including increasing information transparency, easy data access, accelerating the reporting process, time efficiency, and reducing paper use. However, there are still obstacles in implementing the JIBAS application due to limited servers, skilled human resources, and inadequate funding.